Pengembangan Model Pencegahan Penyebaran Covid-19 di Warung Kopi Samarinda - Muhammad Sultan; Sunardi Sunardi; Muhlis Muhlis; Ilham Abu; Ridwan Ridwan; Sutrisno Sutrisno (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Coffee shops or cafes have the potential to create crowds of customers and of course have a high risk of spreading Covid-19. Therefore, research is needed that aims to describe the strategy of cafe managers in preventing the spread of Covid-19 and customer perceptions of this strategy. The design of this research is descriptive qualitative with a case study approach. Research informants are cafe managers and loyal customers who are selected by purposive sampling. The research was conducted at the Kastem Coffee, Samarinda City in August 2021. The information collected was analyzed qualitatively. The results obtained information that cafe managers and customers since the pandemic until the research was carried out had still implemented the Covid-19 health protocol. The cafe manager plans to develop models to prevent the spread of Covid-19 in the cafe environment through cross subsidies and mutual assistance to fellow customers. Cafe customers agree and support, have not made a choice, and do not agree with the model development plan. The results of this study can be taken into consideration for managers of similar businesses and other types of businesses in supporting business environment free of Covid-19.